The World in a Wafer: A Geography of the Eucharist as Resistance to Globalization - Cavanaugh, William T. (Modern theology, 1999)
This essay explores Eucharist as resistance to late-capitalist "globalization." Globalization is often touted as the first true realization of catholicity. Globalization is seen as the demise of the nation-state which has caused so much division among peoples. In contrast, I argue that globalization does not signal the decline of the nation-state but the perfection of the modern state's subsumption of local communities under the universal. True catholicity is based in the practice of the Eucharist, which realizes a universal communion but does so only in local Eucharistic communities, thus overcoming the dichotomy of universal and particular.